Quantitative Analysis of Glutathione Utilizing Highly Luminescent Gold Nanoclusters - Wen, He; Yanping, Qu; Shukai, Wu; Soh Fong, Lim; Ling, Mo; Hongyu, Mou; Jibin, Song (Wiley Periodicals, LLC., 2025)
Glutathione (GSH), a pivotal regulator of cellular redox homeostasis, requires precise monitoring for clinical diagnostics. This work develops bovine serum albumin-templated gold nanoclusters (BSA-AuNCs) through in situ chloroauric acid reduction, exhibiting orange fluorescence (λem = 610 nm) with 35.8% quantum yield. Systematic evaluation of pH-dependent and time-resolved quenching behavior revealed optimal GSH detection at physiological pH 7.4 within 3 min. The nanozyme demonstrated linear responsivity from 10 nM to 3 μM (Limit of Detection, LOD = 8.7 nM) and validated applicability in biological matrices (urine/serum) with 98.0%–103.3% recovery rates. This photoluminescent platform enables reliable GSH biomarker quantification, advancing point-of-care testing for oxidative stress disorders.